2011
DOI: 10.1136/thoraxjnl-2011-200131
|View full text |Cite
|
Sign up to set email alerts
|

Primary airway epithelial cultures from children are highly permissive to respiratory syncytial virus infection

Abstract: Background Respiratory syncytial virus (RSV) infection of airway epithelial cells (AECs) is an important initial event in RSV bronchiolitis. AEC immunological responses are thought to be critical in driving the subsequent inflammation in the airway. This study examined viral replication, cytotoxicity and cytokine production in cultures of primary AECs from children compared with responses to RSV infection in an immortalised epithelial cell line and to those from infants with RSV bronchiolitis. Methods RSV repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
(26 reference statements)
0
27
2
Order By: Relevance
“…Mucus secretion increases in both quantity and viscosity and, when mixed with cellular debris and fibrin, severe obstruction of the airway lumen occurs. Airway epithelial cells appear to be highly permissive to RSV, as demonstrated by the high viral replication and the cell cytotoxicity observed after experimental exposure of human bronchial epithelial cells (BECs) to the virus [36]. In air-liquid interface cultures, generated from nasal and bronchial brushes from healthy preschool children, RSV infection appeared to be localised to apical ciliated epithelial cells, with no detectable infection of goblet cells [37].…”
Section: Rsv Infection and Host Immune Responsementioning
confidence: 99%
“…Mucus secretion increases in both quantity and viscosity and, when mixed with cellular debris and fibrin, severe obstruction of the airway lumen occurs. Airway epithelial cells appear to be highly permissive to RSV, as demonstrated by the high viral replication and the cell cytotoxicity observed after experimental exposure of human bronchial epithelial cells (BECs) to the virus [36]. In air-liquid interface cultures, generated from nasal and bronchial brushes from healthy preschool children, RSV infection appeared to be localised to apical ciliated epithelial cells, with no detectable infection of goblet cells [37].…”
Section: Rsv Infection and Host Immune Responsementioning
confidence: 99%
“…It has been shown that RSV infection of human airway epithelial cells (HAECs) induces strong cytokine/ chemokine responses, including production of IL-1b, IL-6, IL-8, IP-10, macrophage inflammatory protein (MIP)-1a, monocyte chemotactic protein (MCP)-1 and RANTES (regulated on activation normal T-cell expressed and secreted) (Fonceca et al, 2012;Ioannidis et al, 2012;Olszewska-Pazdrak et al, 1998;Oshansky et al, 2010;Tristram et al, 1998;Villenave et al, 2011), and these cytokines and released viral proteins influence the host immune response to RSV (Chirkova et al, 2013;Ioannidis et al, 2012;McNamara et al, 2013;Qin et al, 2011). RSV G protein has been shown to impair innate and memory immune responses, such as suppressing production of IFN-b (Shingai et al, 2008), lymphoproliferation of T-cells (Ray et al, 2001), and responsiveness of monocytes/macrophages and dendritic cells (Johnson et al, 2012;Polack et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of genetic polymorphism (mostly single-nucleotide polymorphism [SNP]) for single chemokine and chemokine receptor genes, including IL-8, IL-8 receptor, RANTES, CCR5 receptor (for RANTES and MIP-1a), and their association with RSV disease severity have been so far inconclusive, based on the fact that these studies have not been confirmed in more than one population or have reported conflicting results [reviewed in (170)]. Greater scientific consensus on the other hand exists in the recognition of respiratory epithelial cells as a major initiator and a modifier of host innate responses and inflammation by secreting chemokines in response to RSV infection (75,81,95,183,203). Most of these studies have been performed in cell culture, but some studies have shown RSV-mediated expression of chemokines in airway epithelial cells in vivo (95).…”
mentioning
confidence: 99%
“…At that point, infection may be self-limited or may spread to the lower respiratory tract in part by a cell-to-cell transfer of the virus along intracytoplasmic bridges (96), although the mechanism by which RSV reaches the lower airway is not clearly defined, as the distribution of infected cells in LRTI is patchy. Thus, the epithelium of the respiratory mucosa, the main function of which is to provide a protective physical barrier against injurious inhaled stimuli, is clearly the main target of RSV replication, as shown by studies of infected patients (178,250), experimental murine models (224), and by a variety of different in vitro culture systems (75,185,203,258) (Fig. 1).…”
mentioning
confidence: 99%